Manfaat Implementasi Sistem Informasi Manajemen di Organisasi Bisnis - Anisa Puspita; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2024)
Management Information Systems (MIS) have become an integral component in the operations of modern business organizations. This paper aims to analyze and outline the main benefits obtained by business organizations through the implementation of MIS. MIS not only affects operational efficiency but also influences decision making, reduces operational costs, and improves customer service. This paper will discuss the benefits of MIS and how business organizations can utilize it effectively